Earthquakes and Structures Select Proceedings of 7th ICRAGEE 2021 - Sitharam, T. G.; Kolathayar, Sreevalsa; Jakka, Ravi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This volume presents select papers presented at the 7th International Conference on Recent Advances in Geotechnical Earthquake Engineering and Soil Dynamics. The papers discuss advances in the fields of earthquake engineering connected with structures. Some of the themes include soil structure interaction, dynamic analysis, underground structures, vibration isolation, seismic response of buildings etc. A strong emphasis is placed on connecting academic research and field practice, with many examples, case studies, and best practices. This volume will be of interest to researchers and practicing engineers alike.
Dynamic Analysis of SSI Effects on Underground Structures -- Joint Time Frequency Analysis Based Synthesis of Acceleration-Time History and Response Spectra for Japanese Earthquakes -- Parametric Study on Overturning Moment Ratio of Buildings with Shallow Foundation for Tsunami Loading -- Semi-active Seismic Vibration Control Offshore Jacket Platforms -- Lateral Capacity of Skirted Footing Resting on Level Ground -- A Case Study of LAS Palmas Tailing Dam Failure -- Soil-Structure-Interaction Study and Safety Assessment of Ventilation Stack for Extreme Wind Events -- Soil-Structure-Interaction Study of Nuclear Safety Related Structure Supported on Alluvium Soil Site and Soil-Structure-Interaction Study of Nuclear Safety Related Structure Supported on Alluvium Soil Site and Estimation of Stiffness's of Its Foundation System -- Seismic Vulnerability Assessment of Lifeline Buildings at Gangtok -- Analysis of Knee-Braced, X-Braced Moment Frame for Ductility based Seismic Design.
Keywords: Engineering geology; Geotechnical engineering; Natural disasters; Soil science; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Natural Hazards; Soil Science; Earthquake engineering -- Congresses